Statistical analysis with Excel for dummies - Schmuller, Joseph (Wiley Pub., 2009)
Describes how to use Microsoft Excel in statistical analysis.
Keywords: Microsoft Excel (Computer file); Statistics; Statistics -- Data processing; Statistics -- Computer programs; Electronic spreadsheets; Microsoft Excel (Computer software); Tableurs; Statistique; Logiciels; Statistique; Informatique; Statistique; statistics; MATHEMATICS; Probability & Statistics; General; Statistics; Computer programs; Statistics; Data processing; Statistics; Computer software; Spreadsheet software; dissertations; Academic theses; Thèses et écrits académiques